2018
DOI: 10.1001/jamanetworkopen.2018.1003
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Factors Associated With Inclusive Work and Learning Environments in Health Care Organizations

Abstract: Key Points Question What factors matter for creating inclusive clinical and learning environments within health care organizations? Findings This qualitative analysis identifies 6 modifiable contributors to an inclusive culture and the implications of these factors on the well-being and performance of members of the health care workforce. Meaning Understanding these factors provides health care systems a way to improve inclusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 64 publications
0
57
0
1
Order By: Relevance
“…This conflicting finding may be explained by more pronounced biases in the selection of commentary articles that favour authorship by men in the first and/or last position. Furthermore, these institutional biases have been shown to limit mentorship and sponsorship opportunities for women 58 59. Patton et al 60 found men mentees receive greater sponsorship compared with women mentees from both men and women mentors,60 with women reporting difficulty in finding same-sex mentors 61.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conflicting finding may be explained by more pronounced biases in the selection of commentary articles that favour authorship by men in the first and/or last position. Furthermore, these institutional biases have been shown to limit mentorship and sponsorship opportunities for women 58 59. Patton et al 60 found men mentees receive greater sponsorship compared with women mentees from both men and women mentors,60 with women reporting difficulty in finding same-sex mentors 61.…”
Section: Discussionmentioning
confidence: 99%
“…Additional strategies may include implicit bias training for editors as well as academic mentors and sponsors 63. Mentors have an opportunity to be more deliberate in how sponsorship and other forms of micro-affirmations may be contributing towards gender disparities in career advancement in academia 53 59. As sponsorship that develops organically, rather than formally, can exclude talented individuals, formal institutional sponsorship programmes are integral to supporting women in medicine 64.…”
Section: Discussionmentioning
confidence: 99%
“…The survey respondents reported a number of experiences related to discrimination, particularly microaggressions and unequal performance expectations. 2 A subset of these concerns related to compensation, evaluation, and promotion may be amenable to institutional approaches such as standardized performance evaluations, salary scales, and salary equity analyses. Future studies could test the relationship between standard business practices and perceptions of inclusion.…”
mentioning
confidence: 99%
“…The survey respondents' emphasis on expanding "collegial networks" as a strategy to promote inclusion suggests that low-tech, interpersonal approaches should be developed and tested. 2 Respondents reported that specific interpersonal gestures were interpreted as noninclusive, including not being greeted or not having a door held. Although it is difficult to regulate standards of behavior, institutions could experiment with campaigns to promote kindness, similar to the handwashing campaigns that have been used to promote patient safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation